2008
DOI: 10.1002/humu.20711
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional deregulation and a missense mutation define ANKRD1 as a candidate gene for total anomalous pulmonary venous return

Abstract: Total anomalous pulmonary venous return (TAPVR) is a congenital heart defect in which the pulmonary veins fail to enter the left atrium and drain instead into the right atrium or one of its venous tributaries. Although a genetic basis for TAPVR has long been recognized, no single gene involved in the pathogenesis of this disease has been identified to date. We previously reported a TAPVR patient bearing a de novo 10;21 balanced translocation. In this work, we cloned both translocation breakpoints from this pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 22 publications
1
42
1
Order By: Relevance
“…Additionally, we have found that ANKRD1, a TGF␤/Smad3 target in smooth muscle cells (33), was synergistically induced by Notch activation and TGF␤ signaling in endothelial cells. Interestingly, the association between the disruption of ANKRD1 expression and the pathogenesis of total anomalous pulmonary venous return (TAPVR), a congenital heart defect, has also been suggested in a recent study (48). Here we show that endothelium-specific inhibition of Notch activity by the overexpression of dnMAML1 in vivo blocks EndMT and reduces Smad3 expression in cardiac cushion cells of mouse embryonic hearts, and this impingement of Notch on a second distinct signaling pathway may explain the severe cardiac defects seen in targeted Notch1 mutants (6).…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, we have found that ANKRD1, a TGF␤/Smad3 target in smooth muscle cells (33), was synergistically induced by Notch activation and TGF␤ signaling in endothelial cells. Interestingly, the association between the disruption of ANKRD1 expression and the pathogenesis of total anomalous pulmonary venous return (TAPVR), a congenital heart defect, has also been suggested in a recent study (48). Here we show that endothelium-specific inhibition of Notch activity by the overexpression of dnMAML1 in vivo blocks EndMT and reduces Smad3 expression in cardiac cushion cells of mouse embryonic hearts, and this impingement of Notch on a second distinct signaling pathway may explain the severe cardiac defects seen in targeted Notch1 mutants (6).…”
Section: Discussionmentioning
confidence: 88%
“…Later, ANKRD1/CARP expression has been found to be rapidly induced in cardiomyocytes in response to hypertrophy stimuli, as well as, at heart failure (HF), suggesting an involvement of ankrd1 activities in physiological and pathological remodeling of ventricular myocardium (Aihara et al, 2000;Zolk et al, 2002;Nagueh et al, 2004). Recently, ankrd1 has been identified as a candidate gene that can play a role in congenital heart disease (Cinquetti et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ankrd1 has also been identified as a candidate gene that can play an important role in congenital cardiac (Cinquetti et al, 2008) and skeletal muscle (Bakay et al, 2002;Nakada et al, 2003) disease, as well as in angiogenesis (Boengler et al, 2003), neovascularization (Shi et al, 2005;Samaras et al, 2007) and neurite outgrowth (Stam et al, 2007). In in vivo experimental settings, ANKRD1 is used as a surrogate biomarker of cardiac hypertrophy (Aihara et al, 2000), cardio-toxic damage (Torrado et al, 2004) or skeletal myopathy (Casey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%